Precipitation Changes in Semi-arid Regions in East Asia Under Global Warming - Guan, Xiaodan; Zhu, Kaiwei; Huang, Xiaoqian; Zeng, Xinrui; He, Yongli (Frontiers in Earth Science, 2021)
The semi-arid regions of East Asia are located in the transition area between regions dominated by the monsoon system and by westerly winds; their interaction is the key to understanding precipitation changes, especially in the summer. Our results show that the enhancement of both the monsoon and westerly winds occurs in wet years, leading to stronger convergence and more rainfall. Weakening of both the monsoon and westerly winds occurs in dry years and results in less rainfall. Such interaction between the monsoon and westerlies is not constant; the boundary of their effects is changing all the time. As the monsoon strengthens, it shifts to the west in wet years and covers most of the semi-arid regions, and the negative effect of the El Niño-Southern Oscillation (ENSO) system on precipitation in the semi-arid regions becomes obvious. However, westward expansion has not been evident over the past 70 years in historic data. In the future, the monsoon will obviously expand westward, and the precipitation over the Loess Plateau will gradually increase as the monsoon boundary expand westward until the end of the 21st century. This change indicates that more rainfall will occur in the semi-arid regions of East Asia, which could dramatically change the ecological environment, especially over the Loess Plateau.